Smart trolley based on client server and computer vision - habiby, Gusvito; Muskhir, Mukhlidi; Mukhaiyar, Riki; Habibullah; Luthfi, Afdal (Journal of Industrial Automation and Electrical Engineering, 2024)
Technological advances have significantly changed many aspects of human life, including shopping activity. The modern retail environment must provide extraordinary customer satisfaction in order to remain competitive. With the Smart Trolley, an automated shopping cart integrated with a payment and pricing system, offers solutions to a shopping challenge that can scan the price of goods. The study explores the development and implementation of Smart Trolley based on client-server architecture and computer vision technology. The Smart Trolley is equipped with a mini PC (Raspberry Pi), a barcode scanner, and an LCD display to display the total cost of goods when they are added to the cart. In addition, it supports non-cash payments and can reduce waiting time at the cashier. Server connections allow real-time monitoring by store staff and prevent fraud. The results of the implementation show that Smart Trolley effectively helps consumers to see the prices of goods, imitate the quarters at the cashier, and improve the security of transactions. This innovative solution aims to simplify the shopping experience, providing a more efficient and comfortable process for consumers in a modern market shopping experience